Extremely tough block polymer-based thermoplastic elastomers with strongly associated but dynamically responsive noncovalent cross-links. (5th March 2021) - Kajita, Takato; Tanaka, Haruka; Noro, Atsushi; Matsushita, Yushu; Nozawa, Atsushi; Isobe, Kousuke; Oda, Ryoji; Hashimoto, Sadaharu
Abstract: To develop elastomers with excellent mechanical properties and processability, block copolymer-based thermoplastic elastomers (TPEs) with dynamic noncovalent cross-links have been actively studied in recent years. Most previous studies on such block copolymer-based TPEs have focused on incorporation of hydrogen-bonded cross-links into the block with a glass transition temperature lower than room temperature; however, the difference between the mechanical properties of hydrogen-bonded TPEs and those of other noncovalent-bonded TPEs has been hardly discussed. This work uses the polystyrene- b -polyisoprene- b -polystyrene (SIS) triblock copolymer produced in industry to synthesize hydrogen-bonded (hSIS) and ionically functionalized thermoplastic elastomers (iSIS) and compares their mechanical properties. iSIS is much tougher than hSIS; remarkably, iSIS exhibits an excellent toughness of 480 MJ m −3, because the ionic multiplets in iSIS serve as much more strongly associated but reversible cross-links. Since the elastomers can be produced at industry scale, they have great market potential for becoming next-generation elastomeric materials. Graphical abstract: Image 1 Highlights: Block polymer-based elastomers with noncovalent cross-links were synthesized. ● Noncovalent-bonded elastomers were synthesized via post-polymerization reaction. ● Hydrogen-bonded elastomers were converted into ionically functionalized elastomers. ● Block polymer-based elastomer with ion multiplets was extremely tough (480 MJ m −3 ).